Gibkost' kak fizicheskoye kachestvo - Tumanyan, G. S.; Kharatsidis, S. K. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The purpose of this paper was to consider the main parameters of the flexibility as a physical quality. The authors analyse the factors, determining the flexibility's manifestations, the ways of flexibility's measuring. The offered classification of flexibility's quality is based on its main signs: the regime of muscle fibres' work, and the presence or the absence of the external aid, when performing an exercise. The next kinds of flexibility are representing, basing on that methodology: dynamic, static, active, passive, active static, active dynamic, passive static, passive dynamic, dosed passive-static, maximal passive-static, dosed passive-dynamic, and maximal passive-dynamic.